IMMIGRANT CULTURAL IDENTITY REPRESENTATION IN JUST GET MARRIED FILM PROMOTION BOOKLET - Ali, Ahmad Jum'a Khatib Nur (Journal of Language and Literature, 2021)
Germany is well known for its welfare and multiculturalism. Just Get Married was produced to capture one’s perspective of immigrant life in Germany. This research aims is to identify the cultural identity representation of immigrants in the booklet of "Just Get Married". This research employs qualitative research and uses promotion booklet as the primary source of data. Hall's representation theory is used as tool of analysis toward the written and visual text structure. The results of this study found that the representation of immigration status in film promotion can be viewed from both civil (political) and cultural perspectives. The analysis result shows how the two sides are intertwined. In Germany, immigrants with non-European cultural descent find it more difficult to obtain nationality or naturalization.